Armenia between Europe and Eurasia. A case study of the Armenian regional integration strategy in the 21st century - Bussas, Inga (2018)
Throughout the 2010s, an increasingly competitive regionalism has complicated the maintenance of the Armenian foreign policy strategy of complementarity. On the eve of the Third Eastern Partnership Summit in Vilnius in 2013, then president Serzh Sargsyan abruptly ended the EU accession and instead, announced his country’s aspirations to join the Eurasian Customs Union which would later become the Eurasian Economic Union. Faced with an ‘ei-ther or’ decision, president Sargsyan opted for the Eurasian path of integration in order to se-cure his own stay in power, while remaining under the Russian security umbrella. Albeit scholars have mostly addressed this issue in the frame of geopolitics and the old Cold War narrative, this thesis argues for a shifting analytical focus from the external to the internal dimension. Outlining the key economic and political factors that have shaped the Armenian regional integration strategy, it takes into account the impact of the particularities of patronal presidential rule on policy-making in post-Soviet Armenia. Against this backdrop, this thesis argues for the potential usage of regional integration as a means of regime survival.